Pterostilbene, a natural phenolic compound, synergizes the antineoplastic effects of megestrol acetate in endometrial cancer. Issue 1 (December 2017) - Wen, Wei; Lowe, Gina; Roberts, Cai; Finlay, James; Han, Ernest; Glackin, Carlotta; Dellinger, Thanh
Abstract Endometrial cancer is the most common gynecologic cancer in the United States and its incidence and mortality has been rising over the past decade. Few treatment options are available for patients with advanced and recurring endometrial cancers. Novel therapies, which are frequently toxic, are difficult to establish in this patient population which tends to be older and plagued by comorbidities such as diabetes mellitus and hypertension. Therefore, novel, non-toxic therapies are urgently needed. Megestrol acetate is a frequently used drug in endometrial cancer patients. However, its response rate is only 20–30%. To enhance the activity of megestrol acetate in endometrial cancer patients, we explored the potential of combining natural supplements with megestrol acetate and found that the addition of the natural phenolic compound, pterostilbene, to megestrol acetate resulted in a synergistic inhibition of cancer cell growthin vitro and an enhanced reduction of tumor growth in a xenograft mouse model. In addition, dual treatment led to attenuation of signaling pathways, as well as cell cycle and survival pathways. Our results demonstrated for the first time that the anti-tumor activity of megestrol acetate can be enhanced by combining with pterostilbene, providing an insight into the potential application of pterostilbene and megestrol acetate combination for the treatment of endometrial cancer.